Correlation between Incidence of Diarrhea in Toddlers and Housewife’s Clean and Healthy Lifestyle - Alamsyah, Teuku; Marianthi, Dewi (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2020)
Diarrhea is one of the public health problems, particularly in infants. Based on the outcomes of the Aceh Besar fitness service survey, Baitussalam sub-district is one of the districts with a excessive wide variety of diarrhea cases, with a total of 520 instances in the one year. This is due to the lack of exact hygiene conduct related to hand washing cleaning soap in the prevention of diarrhea in toddlers. This research ambitions to find out the relationship between the clean and healthy lifestyle housewives on behavior of smooth water use and waste management with diarrhea in children of Baitussalam Subdistrict in Aceh Besar District, Indonesia. This is a descriptive analytic study using a case control study, consist of 28 moms who have children who suffer from diarrhea, and 28 moms who have youngsters do not go through from diarrhea. This lookup resulted in three findings namely there is a relationship between handwashing with cleaning soap with the incidence of diarrhea in infants (p-value 0.003 < α = OR 3.50), there is no relationship between the use of smooth water with the incidence of diarrhea in babies (p-value 1.00 > α = 0.05, OR 1.22) and there is a management relationship with the incidence of diarrhea in teens under five (p-value 0.01 < α = 0.05, OR 4.50).